Análisis comportamental de las leyes de newton - Miguel, O. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
The aim of this paper is to present a didactic view of Newton's lows with particular emphasis on the analysis of the most usual sources of error in their understanding.